IKK∊-Mediated Tumorigenesis Requires K63-Linked Polyubiquitination by a cIAP1/cIAP2/TRAF2 E3 Ubiquitin Ligase Complex - Alicia Y. Zhou (Cell Reports, 2013)
IκB kinase ∊ (IKK∊, IKBKE) is a key regulator of innate immunity and a breast cancer oncogene, amplified in ∼30% of breast cancers, that promotes malignant transformation through NF-κB activation. Here, we show that IKK∊ is modified and regulated by K63-linked polyubiquitination at lysine 30 and lysine 401. Tumor necrosis factor alpha and interleukin-1β stimulation induces IKK∊ K63-linked polyubiquitination over baseline levels in both macrophages and breast cancer cell lines, and this modification is essential for IKK∊ kinase activity, IKK∊-mediated NF-κB activation, and IKK∊-induced malignant transformation. Disruption of K63-linked ubiquitination of IKK∊ does not affect its overall structure but impairs the recruitment of canonical NF-κB proteins. A cIAP1/cIAP2/TRAF2 E3 ligase complex binds to and ubiquitinates IKK∊. Altogether, these observations demonstrate that K63-linked polyubiquitination regulates IKK∊ activity in both inflammatory and oncogenic contexts and suggests an alternative approach to targeting this breast cancer oncogene.